The Relationship Between Smartphone Addiction, Sleep Quality, and Academic Achievement Among Medical Students - Susanto, Vivian Rosiana; Ritunga, Imelda; Nugraheni, Elizabeth Sulastri (Universitas Ibn Khaldun Bogor, 2025)
Smartphone addiction was common among students and could affect sleep quality. Medical students tended to have poor sleep quality due to high academic demands. Smartphone addiction and inadequate sleep quality were known to negatively impact academic achievement. Aims: The purpose of this study was to understand the relationship between smartphone addiction, sleep quality, and academic achievement among medical students at Universitas Ciputra Surabaya. Methods: This research was a quantitative, analytical observational, and cross-sectional study. The population consisted of 3rd, 5th, and 7th-semester medical students at Universitas Ciputra Surabaya. The research sample involved 118 respondents. Smartphone addiction was measured using the SAS-SV, sleep quality was assessed through the PSQI, and academic achievement was determined by MCQ scores. The study was analyzed using the chi-square test and contingency coefficient. Results: The study found no significant relationship between smartphone addiction and sleep quality (p = 1.0) or between sleep quality and academic achievement (p = 0.340). However, there was a weak positive correlation between smartphone addiction and academic achievement (p = 0.036). Additionally, no significant combined effect of smartphone addiction and sleep quality on academic achievement was identified (p = 0.058). Conclusion: While a weak positive association existed between smartphone addiction and academic achievement, there was no evidence of a relationship between sleep quality and academic achievement among medical students.